Kryteria administracyjnego podziału kraju z punktu widzenia struktury regionalnej - Parysek, Jerzy (Wydział Prawa i Administracji UAM, 1993)
In the near future important changes in the administrative division of Poland will be implemented. Such a step is reasonable only when it brings about advantages which would otherwise be unavailable or hard to achieve. The structure of territorial division of the state should consist of socio-economic key regions arranged hierarchically. Such units should be of key character and they should have a distinct center of a given rank. Furthermore, they should have a high degree of density of population as well as of social, economic and cultural integration. Besides, they should be characterized by a considerable level of self-organization and they should have strong internal territorial links. Besides, each regional division should meet the criteria of adequacy and separation. The elements of such regional structure should be: (1) communes (gminy), as basic units of the regional structure of the state and basic territorial units of the socio-economic links of local character; (2) districts (powiaty), as sub-regional units consisting of communities, strongly linked with the sub-regional center; (3) regions (województwa), as the conglomeration of provinces, strongly linked with the regional centre. Any discussion on the number of units of the territorial division of the state has little sense before the appropriate research has been carried out. The territorial division should be accompanied by a clear determination of powers vested in particular units and by a considerable decentralization of the state powers (including the shifting of some central institutions to the regional level). The change of the territorial division of the state must be done simultaneously and in one stage, i.e., districts and regions (larger than they are today) must be created at the same time. It is a difficult and demanding task; therefore, it should be carefully prepared and its results should last for several decades.
Criteria of administrative division of the state from the point of view of a regional structure